Short-course antibiotic therapy for hospitalized patients with early clinical response in community-acquired pneumonia: a multicentre cohort study. (January 2023) - Israelsen, Simone Bastrup; Fally, Markus; Tarp, Britta; Kolte, Lilian; Ravn, Pernille; Benfield, Thomas
Abstract: Objectives: To explore whether short-course antibiotic therapy is efficient and safe in routine clinical settings among patients hospitalized with community-acquired pneumonia (CAP) who achieve an early clinical response. Methods: During 2017–2019, we conducted a cohort study of patients admitted with CAP to four hospitals in Denmark. Data were prospectively gathered from medical records and enriched with data from nationwide registries. In the present study, we included patients with early clinical response and divided them into treatment groups based on antibiotic duration, as decided by the attending physician: short-course (4–7 days) or prolonged-course (8–14 days). The primary outcome was post-treatment mortality within 30 days. Secondary outcomes included readmissions or new antibiotics. Logistic regression models were used to estimate ORs with 95% CIs, and inverse probability weighting was applied to adjust for confounding. Results: The study cohort included 1151 patients with a median age of 74 years, predominantly presenting with mild-moderate disease. The 30-day post-treatment mortality was 3.36% (11/327) in the short-course group and 3.40% (28/824) in the prolonged-course group (adjusted OR 1.05, 95% CI 0.38–1.88). Readmission occurred in 15.6% (42/269) vs. 14.0% (102/727) (adjusted OR 1.07, 95% CI 0.75–1.69) and new prescription of antibiotics in 11.9% (32/269) vs. 12.1% (88/727) (adjusted OR 0.99, 95% CI 0.61–1.49). Discussion: In patients hospitalized with CAP and early clinical response, similar outcomes were observed between short-course and prolonged-course therapies. These results support the use of short-course therapy in routine clinical settings.